2022
DOI: 10.1096/fj.202101897r
|View full text |Cite
|
Sign up to set email alerts
|

Dawn and dusk peaks of outer segment phagocytosis, and visual cycle function require Rab28

Abstract: RAB28 is a farnesylated, ciliary G‐protein. Patient variants in RAB28 are causative of autosomal recessive cone‐rod dystrophy (CRD), an inherited human blindness. In rodent and zebrafish models, the absence of Rab28 results in diminished dawn, photoreceptor, outer segment phagocytosis (OSP). Here, we demonstrate that Rab28 is also required for dusk peaks of OSP, but not for basal OSP levels. This study further elucidated the molecular mechanisms by which Rab28 controls OSP and inherited blindness. Proteomic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 68 publications
(206 reference statements)
0
19
0
Order By: Relevance
“…A similar profile is observed in zebrafish, albeit raised under a different environmental light–dark cycle of 14 h light: 10 h dark. 2 prominent OSP peaks occur, the first after light exposure, and a second shortly after darkness 16,28 . In contrast to the goldfish study, the zebrafish were shown by immunolabeling to display mixed rod and cone OSP peaks, with the morning peak slightly favoring the phagocytosis of distal rod cell OS tips and the evening peak favoring the phagocytosis of distal cone cell OS tips 16 …”
Section: Diversity Of Rhythmic Osp Peaks In Different Speciesmentioning
confidence: 79%
See 3 more Smart Citations
“…A similar profile is observed in zebrafish, albeit raised under a different environmental light–dark cycle of 14 h light: 10 h dark. 2 prominent OSP peaks occur, the first after light exposure, and a second shortly after darkness 16,28 . In contrast to the goldfish study, the zebrafish were shown by immunolabeling to display mixed rod and cone OSP peaks, with the morning peak slightly favoring the phagocytosis of distal rod cell OS tips and the evening peak favoring the phagocytosis of distal cone cell OS tips 16 …”
Section: Diversity Of Rhythmic Osp Peaks In Different Speciesmentioning
confidence: 79%
“…This dysregulation of OSP also occurs in genetic models. In Rab28 and Kif17 knockout zebrafish and mice, the peak levels of OSP become reduced 16,28 . OSP peaks can also be increased in amplitude.…”
Section: Regulation Of Osp Timing Amplitude and Entrainmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A robust morning peak shortly after light onset and low activity at other times is a rhythm that has been reported for over 50 years in laboratory mice and rats that are entrained to a 12 h light–12 h dark cycle, i.e., with light on from zeitgeber time 0 (ZT0) to ZT12 and light off from ZT12 to ZT0 [ 4 , 5 , 6 ]. Recently, a previously unseen evening peak of rod POS phagocytosis following onset of darkness has been reported in both mice and zebrafish [ 7 , 8 , 9 ]. In these studies, both electron microscopy and rhodopsin immunofluorescence microscopy were used to identify and quantify POS phagosomes in the RPE in situ.…”
Section: Introductionmentioning
confidence: 99%